Balloon-Catheter Buddy Technique for Coiling of Very Small Aneurysm - Vikas Bhatia; Bharat Hosur; Ajay Kumar (Journal of Clinical Interventional Radiology ISVIR)
The catheter movement and stability in coiling of very small aneurysms is challenging. We describe a technique for controlled catheter movement and successful coiling of a very small aneurysm.